2016
DOI: 10.2169/internalmedicine.55.6207
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of In-line Filters in Central Venous Catheters Does Not Significantly Influence the Incidence of Bloodstream Infections and Mortality in a Hospital Hematological Ward

Abstract: Objective The use of intravenous in-line filters is effective for the mechanical removal of large particles, precipitates, bacteria, fungi, large lipid globules, and air. However, the routine use of in-line filters remains controversial. Many patients with hematological diseases frequently suffer from bloodstream infections (BSIs) with fatal outcomes. Methods The year before cessation of an in-line filter was defined as the "filter period" and the year after its cessation was defined as the "non-filter period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Some studies showed a benefit, and others could not prove the significance of filter use. Two systematic reviews, one observational study, and one clinical trial have failed to prove the effectiveness of filters significantly in reducing complications, and also doubt the value of the filter (Foster et al, 2015;Niël-Weise et al, 2010;Tanaka et al, 2016;Virlouvet et al, 2020). However, some studies have been performed under ideal conditions, considered well-controlled and compliant to protocols so the incompatibilities were not identified.…”
Section: In-line Filtration For Trapping Precipitatesmentioning
confidence: 99%
“…Some studies showed a benefit, and others could not prove the significance of filter use. Two systematic reviews, one observational study, and one clinical trial have failed to prove the effectiveness of filters significantly in reducing complications, and also doubt the value of the filter (Foster et al, 2015;Niël-Weise et al, 2010;Tanaka et al, 2016;Virlouvet et al, 2020). However, some studies have been performed under ideal conditions, considered well-controlled and compliant to protocols so the incompatibilities were not identified.…”
Section: In-line Filtration For Trapping Precipitatesmentioning
confidence: 99%
“…Duration of Project Trail 2 months in PICU, with continuous feedback from the end users and other health care providers [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…63 For instance, in-line filters did not significantly influence the incidence of bloodstream infections, phlebitis, morbidity, and mortality. [64][65][66] Nevertheless, according to most national recommendations in Europe, there is a role for the use of in-line filtration of TNA for patients who require intensive parenteral therapy; the immunocompromised, neonates, and children might have increased susceptibility to the detrimental effects of particulate contamination and therefore can benefit from the use of filters during the administration of PN. 31,33,[67][68][69] In such cases, 0.22-μm filters should be used for lipid-free admixtures and 1.2-μm filters for lipidcontaining admixtures.…”
Section: Ile Administrationmentioning
confidence: 99%